Intersecting constraints: Exploring labour market barriers for urban women in Sub-Saharan Africa - Alexander Stöcker (German Institute of Development and Sustainability (IDOS), 2025)
This study examines the determinants of female labour force participation (FLFP) and female wage employment (FWE) of urban women in four SSA countries: Benin, Senegal, Uganda and Zambia. Using extensive micro-level data and a unified empirical framework, we investigate the multitude of constraints women face in both these dimensions. The methodology tries to bridge the drawbacks of typical macro-level cross-country studies and detailed country case studies, enabling direct comparisons over time and across countries. Key findings highlight substantial cross-country heterogeneity in barriers to female employment, including education, household wealth, motherhood, and male breadwinner norms. While higher education consistently enhances FLFP and FWE, motherhood negatively affects wage employment more persistently than labour force participation. Interaction effects between barriers, such as motherhood and male breadwinner norms, underscore their compounded impact. Additionally, local labour market conditions, namely the variety of occupations available, moderate these barriers, amplifying disadvantages for women in labour markets with higher levels of occupational variety. The study emphasises the importance of context-specific policy interventions. Recommendations include vocational training in Benin, advocacy for shifting restrictive norms in Senegal, targeted support for labour market transitions in Uganda, and addressing male breadwinner norms in Zambia. Future research should delve deeper into how labour market transitions influence female employment and how negative consequences can be remedied.
Keywords: 320; Female Labour Force Participation; Wage Employment; Gender Equality; Sub-Saharan Africa; Employment Barriers; Context-Specific Policies